Library Orientation Methods: J. Hillis Miller Health Center Library Program - Eaton, Elizabeth S. (1972)
Two orientation devices are described which are currently in use at the J. Hillis Miller Health Center Library. One is a taped tour which requires a portable recorder with earphones attached. Tapes are now available for nursing students, physical therapy students, and Health Center staff. The tour includes location information and description of the card catalog and certain basic index and abstract services. The second orientation device is a short instruction tape on the use of Index Medicus which is attached to the Index Medicus table. This is heard through a telephone apparatus. It is anticipated that the tape technique will be expanded to apply to other students and other library tools. It is also believed that this technique may be used in other libraries. Information about the supplies and equipment used is given as an addendum.